Maklumat leksikal dalam struktur kasus dan argumen dalam penulisan berita (Jurnal Bahasa, 2006)
This study will attempt to justi& the role played by semantic features of certain verbs of Malay language to the number of deep cases and the possible arguments appeared in a sentence structure at superficial level. The writers of this study use the concept of semantic features of a verb used popularly by Charles J. Fillmore along with his terminological term: "lexical information" . To him, a basic sense of a word is expressible as a set of components that are complex as they may be required to character-ize events or situations. In this study the writers will sample certain ele-mentary semantic properties of verbs, especially those relating to time, space, movement and "will" . The study will try to show the flexibility of certain verbs in the number of arguments they take in the predicate struc-ture. The verb and conceptually require three arguments, namely those identifiable as the culprit, the loser; and the loot. The words and are each four — argument predicates, the arguments representing the one who receives the goods or services, the one who provides the goods and services, the goods and services themselves, and the sum of money that changes hands. In gramniatical descriptions, we try to identify the role structure of given expressions. From here the writ-ers go further to prove the roles that their arguments play are taken from an inventory of role types fixed in case structure by grammatical theory. The application of case theory, with their separate arguments associated with certain verbs as used in the writing of news as rhetorical discourse is being looked at, in an attempt to see that the grammar of news written language is found to be similar to that used in descriptions. The number of arguments allowed in sentence structures seems to be identifiable within the domain of their semantic interpretation of cases used in the writing of news in Malay daily newspapers.